Roberts and Hedges' clinical procedures in emergency medicine - Roberts, James R. 1946-; Custalow, Catherine B.; Thomsen, Todd W.; Hedges, Jerris R. (Elsevier/Saunders, 2014)
Covers the equipment, devices, drug therapies, and techniques you need to know for effective practice of emergency medicine.